2012
DOI: 10.1039/c2gc35238a
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing applied potential to oxidation in water

Abstract: Oxidation is one of the most important types of transformation in chemistry, and practical mild oxidation without added reagents or solvents has been a long-standing challenge. We have developed a highly practical solvent-free (biphasic) electrochemically driven oxidation system for the selective conversion of sulfides to the corresponding sulfoxides, and alkenes to the corresponding epoxides, in a very simple reactor system. Excellent yields are obtained for a variety of substrates, and neither over-oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…The lipid double bonds can be electro‐epoxidized in the presence of hydrochloric acid and an acetonitrile/water solvent system in a nanoESI emitter with a large orifice (Figure ; the effect of orifice size will be discussed below) which serves as an electrochemical cell. We reasoned that the addition of chloride in an acidic environment might introduce a superior oxidative pathway by in situ formation of hypochlorite and conversion of double bonds into the corresponding epoxides (see Section S3 in the Supporting Information for electro‐epoxidation reagent study and optimization of HCl concentration). The voltage applied to the nanoESI working electrode plays two roles: 1) it initiates electrospray; and 2) it initiates/terminates electro‐epoxidation of lipid double bonds.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The lipid double bonds can be electro‐epoxidized in the presence of hydrochloric acid and an acetonitrile/water solvent system in a nanoESI emitter with a large orifice (Figure ; the effect of orifice size will be discussed below) which serves as an electrochemical cell. We reasoned that the addition of chloride in an acidic environment might introduce a superior oxidative pathway by in situ formation of hypochlorite and conversion of double bonds into the corresponding epoxides (see Section S3 in the Supporting Information for electro‐epoxidation reagent study and optimization of HCl concentration). The voltage applied to the nanoESI working electrode plays two roles: 1) it initiates electrospray; and 2) it initiates/terminates electro‐epoxidation of lipid double bonds.…”
Section: Figurementioning
confidence: 99%
“…In this work, we present anovel electrochemical strategy for characterizing double-bond positions in unsaturated lipids.T he lipid double bonds can be electro-epoxidized in the presence of hydrochloric acid and an acetonitrile/water solvent system in an anoESI emitter with al arge orifice ( Figure 1; the effect of orifice size will be discussed below) which serves as an electrochemical cell. We reasoned that the addition of chloride in an acidic environment might introduce as uperior oxidative pathway by in situ formation of hypochlorite and conversion of double bonds into the corresponding epoxides [23] (see Section S3 in the Supporting Information for electro-epoxidation reagent study and optimization of HCl concentration). Thev oltage applied to the nanoESI working electrode plays two roles:1 )iti nitiates electrospray;a nd 2) it initiates/terminates electro-epoxidation of lipid double bonds.I nterestingly,t he epoxidation of lipid double bonds can be well-controlled by tuning the applied voltage while maintaining the electrospray plume.As aresult, the lipid epoxidation can be switched off by applying av oltage of 2.5 kV,a nd counter-intuitively switched on by reducing the voltage to 1.8 kV ( Figure 1).…”
mentioning
confidence: 99%
“…We have recently shown that electrosynthesis can be a powerful tool for a range of important reactions[ 16 ] and can be employed in the catalyst-free synthesis of five-membered ring cyclic carbonates under atmospheric pressure carbon dioxide and mild temperatures. [ 17 ] The importance of six-membered ring cyclic carbonates and their inherent thermodynamic instability prompted us to investigate this important carbon dioxide insertion reaction.…”
Section: Introductionmentioning
confidence: 99%
“…32 The asymmetric epoxidation processes utilizing iminium salt catalysts 1 and 2 have been used in syntheses of levcromakalim, 33 (−)-lomatin and (+)-trans-khellactone, 34 scuteflorin, 35 and mollugin,. 36 Alternative oxidants, such as hydrogen peroxide or sodium hypochlorite, 37 and electrochemically generated oxidants 38 may also be used in these iminium salt-catalyzed epoxidation reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alternative oxidants such as hydrogen peroxide or sodium hypochlorite, 37 and electrochemicallygenerated oxidants, 38 may also be used in these iminium salt-catalysed epoxidation reactions.…”
mentioning
confidence: 99%